Experimental Study on Vacuum Ice-temperature Measurement of Fruits and Vegetables - Wang Ying; Zheng Xunzhou; Ma Xianping (Zhileng xuebao)
Since vacuum ice-temperature preservation technology combines ice-temperature preservation and vacuum preservation, it is called the third generation preservation technology of agricultural product. The key to achieving this technology is to measure the ice-temperature of fruits and vegetables under vacuum pressure. In this paper a large number of experiments about the ice-temperature of tomatoes and peppers under different vacuum pressures were conducted, and the ice-temperature of the two fruits and vegetables under atmospheric pressure、0.08MPa、0.06MPa、0.04MPa were measured, based on which the ice-temperature formulas were fitted. The experimental results show that different storage pressures have different impact on the ice-temperature trends of fruits and vegetables.